A GREEN ENTREPRENEURSHIP BASED MODEL: THE SYNERGISTIC EFFECTS OF ENTREPRENEURIAL ORIENTATION AND ECOPRENEURSHIP ON MARKETING PERFORMANCE OF CULINARY SMES IN CIMAHI CITY - Dhameria, Vita (Jurnal Riset Bisnis dan Manajemen, 2026)
This study examines the effects of entrepreneurial orientation and ecopreneurship on the marketing performance of small and medium-sized culinary businesses in Cimahi City, with competitive advantage as a mediating variable. Using a quantitative approach, data were collected through questionnaires from 120 culinary entrepreneurs and analyzed using Structural Equation Modeling (SEM). The findings indicate that ecopreneurship has a strong and positive effect on both competitive advantage and marketing performance. Competitive advantage significantly enhances marketing performance. In contrast, entrepreneurial orientation contributes positively to competitive advantage but does not have a direct and significant effect on marketing performance. Overall, the results highlight the crucial role of ecopreneurship and competitive advantage in improving marketing performance. Therefore, culinary SMEs are encouraged to emphasize innovation and environmentally friendly business practices to strengthen competitiveness and achieve sustainable marketing outcomes.